The Auditory Processing Deficiencies in People Who Stutter: A Narrative Review - Parisa Zare; Fatemeh Jafarlou; Fatemeh Fekar-Gharamaleki (Vesnu Publications, 2020)
Introduction: Stuttering is a multifactorial disorder. So far, numerous findings have been reported regarding various deficits in auditory processing components in the people who stutter. Despite studies on correlation of auditory processing deficits and stuttering, this assumption has not been proven yet. The purpose of the present study was to investigate and collect the results of studies regarding the auditory processing deficits in the people who stutter.Materials and Methods: This study was a narrative review to collect research on auditory processing deficits in people who stutter. ISI, PubMed, Scopus, Science Direct, and PsycINFO databases were searched to reterive English articles that were published from 1995 to 2020. For studies conducted in Iran in Persian, SID and Magiran databases were searched. "Stuttering", "auditory feedback processing", "neurophysiology", and "brain maturity" were the keywords of interest.Results: In the first stage, 211 articles were found. Finally, after reviewing the inclusion criteria, 86 articles in English and Persian were included. In addition to reviewing articles concerning the existence of auditory processing deficits, the present study emphasized that auditory processing problems in the people who stutter altered the assessment, diagnosis, and treatment approaches.Conclusion: Although there is no evidence of anatomical abnormalities in the auditory system of people who stutter, numerous studies have reported unstable evidence of central impairments in their auditory processing. Neuroimaging and electrophysiological studies showed involvement of the central and peripheral areas of auditory processing.